A skutterudite thermoelectric material electrode and a method for connecting a skutterudite thermoelectric material and an electrode
A novel electrode formation method using aluminum-based powders creates a dense, crack-free bond with skutterudite thermoelectric materials, addressing inefficiencies and cost issues in existing connection methods, improving device reliability and efficiency.
Patent Information
- Application Number
- CN202210063653.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-01-20
AI Technical Summary
Existing methods for connecting skutterudite thermoelectric material electrodes are inefficient, unstable, complex, costly, and require significant equipment investment, leading to poor reliability and high interface resistance in harsh environments.
A method using aluminum powder, aluminum oxide powder, and ammonium chloride powder to form an aluminum-rich intermetallic compound electrode on the skutterudite thermoelectric material surface through vacuum calcination, ensuring a dense and crack-free bond.
The method provides a rapid, efficient, and cost-effective connection with improved interface bonding, suitable for large-scale production, enhancing the reliability and efficiency of thermoelectric devices.
Smart Images

Figure CN114497335B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a skutterudite thermoelectric material electrode and also to a method for connecting the skutterudite thermoelectric material and the electrode, belonging to the technical field of thermoelectric power generation. Background Art
[0002] Thermoelectric power generation technology is a technology that directly converts thermal energy into electrical energy through the Seebeck effect. Thermoelectric power generation devices have been widely used in deep space exploration power supplies and special military power supplies due to their advantages such as small size, no moving parts, no noise, no pollution, no maintenance, and long life. At the same time, in the fields of industrial waste heat and automobile exhaust waste heat recovery, thermoelectric power generation devices also have broad application prospects and potential social and economic benefits.
[0003] Since most thermoelectric devices usually work under harsh environmental conditions, such as high temperature, large temperature difference, broadband vibration, and extremely long working time, the long-term reliability of the device has become a major obstacle to industrial application. El-Genk et al. found that the output power of the skutterudite device with Cu as electrode decreased by 70% after 150 days of accelerated test at 600℃, and the sharp increase in the contact resistivity of the high-temperature end interface was the main reason for the decline in device performance. The heterogeneous interface between the thermoelectric material and the electrode plays a key role in the reliability of the device. For devices used in medium and high temperature power generation, the selection and connection technology of high-temperature electrode materials are particularly difficult due to their high operating temperature. Among them, as one of the most promising candidates in the medium temperature zone, CoSb3-based skutterudite thermoelectric devices have an extremely high conversion efficiency of up to 12%. At present, the main ways to connect the electrode to the CoSb3-based skutterudite thermoelectric material are spring pressure contact, brazing, and sintering. NASA-JPL proposed a spring pressure contact method to prepare CoSb3-based thermoelectric power generation devices in the early stage, but the simple mechanical contact resulted in large interface resistance and interface thermal resistance, which hindered the improvement of device efficiency (El-Genk MS, Saber HH, Caillat T. Efficient segmented thermoelectric unicouples for space power applications [J]. Energy Conversion & Management, 2003, 44 (11): 1755-1772.). As for the brazing method, due to the serious mutual diffusion between the solder and the substrate and the poor stability, it is difficult to meet the requirements of long-term use. Fan et al. used Ti as a transition layer and adopted a two-step SPS method to connect the Mo electrode to the CoSb3 material. However, due to the large difference in the thermal expansion coefficients of Mo and CoSb3, the residual stress at the interface was large and cracks were easily generated, affecting the bonding strength and reliability of the device (Fan J, Chen L, Bai S, et al. Joining of Mo to CoSb3 by spark plasma sintering byinserting a Ti interlayer[J]. Materials Letters, 2004, 58(30):3876-3878.).Later, this technology was used to optimize the alloy composition through Mo-Cu alloying. The thermal expansion coefficient of Mo-Cu can be adjusted to match that of CoSb3-based filled cooperite, the interface residual stress is greatly reduced, and the interface strength and device reliability are improved (Zhao D, LiX, He L, et al. Interfacial evolution behavior and reliability evaluation ofCoSb3 / Ti / Mo-Cu thermoelectric joints during accelerated thermal aging[J].Journal of Alloys & Compounds, 2009, 477(1-2):425-431.). However, this method has high requirements for equipment and molds, it is not easy to obtain high economic benefits, and the thickness of the transition layer is not easy to control. Therefore, a low-cost, efficient and reliable connection method still needs to be developed. Summary of the invention
[0004] In view of the shortcomings of the existing connection method between skutterudite thermoelectric material and electrode, such as low efficiency, poor stability, complex process, large equipment investment and high cost, the present invention provides a skutterudite thermoelectric material electrode and a connection method of the electrode and the skutterudite thermoelectric material. The connection method between the electrode and the skutterudite thermoelectric material of the present invention is simple, short in time, high in efficiency, small in equipment investment and low in cost, which greatly improves the connection efficiency of the skutterudite thermoelectric material electrode. The obtained electrode is tightly connected to the skutterudite thermoelectric material, has no cracks, has controllable thickness, has a firm interface, and can well play the role of the electrode.
[0005] The specific technical solutions of the present invention are as follows:
[0006] A skutterudite thermoelectric material electrode is made of the following raw materials in percentage by mass: 25-35% aluminum powder, 3-5% ammonium chloride powder, and the balance aluminum oxide powder.
[0007] Furthermore, the raw materials of the electrode are mixed evenly and then vacuum calcined to obtain the electrode. The calcination temperature is generally 500-550° C. and the calcination time is 0.5-2 hours. The composition of the electrode obtained by calcination is an aluminum-rich intermetallic compound.
[0008] The present invention also provides a method for connecting a skutterudite thermoelectric material and an electrode, comprising the following steps:
[0009] (1) putting uniformly mixed aluminum powder, aluminum oxide powder and ammonium chloride powder into a crucible, and then burying the skutterudite thermoelectric material into the mixed powder;
[0010] (2) Place the crucible into a quartz tube and evacuate and seal it;
[0011] (3) The quartz tube is heated to a calcination temperature and calcined. After calcination, the skutterudite thermoelectric material is taken out and an electrode layer is obtained on its surface, thereby achieving connection between the skutterudite thermoelectric material and the electrode.
[0012] Further, the skutterudite thermoelectric material composition of the present invention refers to pure CoSb3, or a doped CoSb3 material formed by filling or doping other elements in CoSb3 as a matrix, and the doped elements can be one or more of Yb, Li, Ir, Na, K, Ca, La, Al and Pd. The skutterudite thermoelectric material is generally in bulk.
[0013] Furthermore, the crucible is a graphite crucible.
[0014] Furthermore, in step (1), the raw materials of the electrode are aluminum powder, aluminum oxide powder and ammonium chloride powder, the content of aluminum powder is 25-35wt%, the content of ammonium chloride powder is 3-5wt%, and aluminum oxide powder makes up the balance, and the sum of the three is 100wt%. Among them, aluminum powder provides the elements required for the electrode layer, aluminum oxide powder plays the role of dilution filling and preventing aluminum powder from sticking, and ammonium chloride powder can promote the generation of active aluminum atoms and accelerate the growth rate of the electrode layer. The content of aluminum powder should not be too high or too low. If it is too low, it is not easy to form a continuous electrode layer. If it is too high, it is easy to cause aluminum powder to stick, reducing the utilization rate of aluminum powder. The content of ammonium chloride powder should not be too high. If it is too high, the quality of the electrode layer will be reduced, and excessive consumption of aluminum source will cause waste.
[0015] Furthermore, the particle size of the aluminum powder is less than or equal to 10 microns, and its purity is greater than or equal to 99.85%; the particle size of the aluminum oxide powder is less than or equal to 1 micron, and its purity is greater than or equal to 99.99%. The ammonium chloride powder is AR grade.
[0016] Furthermore, in step (1), the aluminum powder, aluminum oxide powder, and ammonium chloride powder can be mixed uniformly in advance by conventional physical mixing methods such as stirring and grinding, and can be mixed by dry mixing or wet mixing. Preferably, the wet mixing method is adopted, the three powders are put into a mortar, anhydrous ethanol is added, and they are manually ground for 10-20 minutes and dried. The addition of anhydrous ethanol can prevent the powders from sticking to each other during the grinding process and causing uneven mixing.
[0017] Furthermore, in step (1), the skutterudite thermoelectric material is buried in the center of the mixture powder, which is conducive to forming a uniform electrode layer.
[0018] Furthermore, in step (2), the crucible is placed in a quartz tube and sealed with vacuum, and the vacuum degree in the quartz tube is above 0.01 MPa to isolate the consumption of aluminum powder caused by oxygen. The present invention must be sealed, otherwise the gas overflow will seriously lead to the inability to form an electrode layer.
[0019] Furthermore, in step (3), the calcination temperature is 500-550°C and the calcination time is 0.5-2h. If the temperature is too low, the electrode layer cannot be formed. If the temperature is too high, there will be more defects inside the electrode layer, which will affect the quality of the electrode layer and easily cause the decomposition of the skutterudite thermoelectric material matrix. The insulation time should not be too long. If the time is too long, the thickness of the electrode layer will not increase significantly, which will cause a waste of energy. If the time is too long, it will also affect the performance of the matrix.
[0020] Furthermore, the heating rate is preferably 5-10°C / min. At this heating rate, the performance of the obtained electrode is better.
[0021] Furthermore, the thickness of the electrode layer is controlled by controlling the content of aluminum powder, ammonium chloride powder and aluminum oxide powder, the calcination temperature and time and other conditions. Generally speaking, within a given range of conditions, the higher the aluminum powder content, the higher the calcination temperature and the longer the time, the thicker the thickness of the obtained electrode layer. The composition of the obtained electrode layer is an aluminum-rich intermetallic compound, and its thickness is generally 15-55 microns. The obtained electrode layer is evenly distributed on the surface of the skutterudite thermoelectric material, the electrode layer is dense and crack-free, and is firmly bonded to the surface of the skutterudite thermoelectric material.
[0022] The present invention has the following beneficial effects:
[0023] The present invention selects aluminum powder, aluminum oxide powder and ammonium chloride powder as electrode raw materials, buries the skutterudite thermoelectric material in the electrode raw materials, reacts and diffuses them at a certain temperature, and directly forms an electrode in situ on the surface of the skutterudite thermoelectric material, thereby realizing the rapid connection between the skutterudite thermoelectric material and the electrode. The obtained electrode is uniform, dense and crack-free, and is metallurgically bonded with the CoSb3 thermoelectric material, with a good interface bonding state. The method of the present invention has the advantages of short production cycle, small equipment investment, simple operation, etc., greatly improves the efficiency of connecting the skutterudite thermoelectric material with the electrode, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the method of the present invention.
[0025] Figure 2 This is the surface distribution diagram of the interface elements at the connection between the electrode and the CoSb3 thermoelectric material in the product prepared in Example 1.
[0026] Figure 3 This is a line scan of the interface elements at the connection between the electrode and the CoSb3 thermoelectric material in the product prepared in Example 1.
[0027] Figure 4 This is a scanning electron microscope photograph of the interface between the electrode and the CoSb3 thermoelectric material in the product prepared in Example 1.
[0028] Figure 5 This is a scanning electron microscope photograph of the interface between the electrode and the CoSb3 thermoelectric material in the product prepared in Example 2.
[0029] Figure 6 This is a scanning electron microscope photograph of the interface between the electrode and the CoSb3 thermoelectric material in the product prepared in Comparative Example 1.
[0030] Figure 7 This is a scanning electron microscope photograph of the interface between the electrode and the CoSb3 thermoelectric material in the product prepared in Comparative Example 2.
[0031] In the figure, 1. quartz tube, 2. graphite crucible, 3. raw material mixed powder, 4. CoSb3 bulk material. DETAILED DESCRIPTION
[0032] In order to further understand the content of the present invention, the present invention is now described in detail in conjunction with specific embodiments.
[0033] In the following examples, the particle size of the aluminum powder used is 10 microns and the purity is 99.85%. The particle size of the aluminum oxide powder used is 1 micron and the purity is 99.99%. The ammonium chloride powder used is AR grade.
[0034] Example 1
[0035] (1) Weigh 20 g of three raw material powders (aluminum powder (25%), alumina powder (71%), and ammonium chloride powder (4%)) by mass percentage. Put the three powders into a mortar, add anhydrous ethanol and grind manually for 10 minutes to mix them evenly, and dry them at 50°C. Then take out 2 g of the mixed powder and put it into a graphite crucible, and place a CoSb3 block material at the center of the powder;
[0036] (2) Slowly place the graphite crucible into the quartz tube, evacuate and seal it, and the vacuum degree should be above 0.01 MPa;
[0037] (3) Place the quartz tube in a tube furnace, set the heating rate to 10°C / min, raise the temperature to 550°C, and keep it at this temperature for 2 hours;
[0038] (4) After the furnace cools to room temperature, take out the sample, put it into an ultrasonic cleaner for ultrasonic cleaning for 5 minutes, and then take out the sample for drying. After roasting, an electrode layer is obtained on the surface of the CoSb3 bulk material, thereby realizing the connection between the cobaltite thermoelectric material and the electrode.
[0039] Figure 2 and 3 It is the interface element surface distribution diagram and interface element line scanning diagram of the obtained electrode / CoSb3 thermoelectric material. It can be seen from the figure that the electrode and the thermoelectric material are metallurgically bonded, element diffusion occurs between the two, and the aluminum element is distributed in the electrode layer with a concentration gradient. The thickness of the electrode layer is about 50 microns.
[0040] Figure 4 This is a scanning electron microscope photograph of the interface of the obtained electrode / CoSb3 thermoelectric material. It can be seen from the figure that the electrode layer is dense and has no cracks, and is well combined with the CoSb3 thermoelectric material.
[0041] Example 2
[0042] An electrode layer was obtained on the CoSb3 bulk material according to the method of Example 1, except that in step (3), the temperature was raised to 500°C at a rate of 10°C / min and calcined at this temperature for 2 hours. The thickness of the obtained electrode layer was about 20 microns.
[0043] Figure 5 This is a scanning electron microscope photograph of the interface of the obtained electrode / CoSb3 thermoelectric material. From the figure, it can be seen that the electrode layer is uniform and dense, the interface is flat and has no cracks, and it is well bonded with the CoSb3 thermoelectric material.
[0044] Example 3
[0045] An electrode layer was obtained on the CoSb3 bulk material according to the method of Example 1, except that in step (3), the temperature was raised to 550°C at a heating rate of 5°C / min and calcined at this temperature for 2 hours. The obtained electrode layer had a thickness of about 50 μm, was uniform and dense, had a flat interface without cracks, and was well bonded to the CoSb3 thermoelectric material.
[0046] Example 4
[0047] An electrode layer was obtained on the CoSb3 bulk material according to the method of Example 1, except that in step (3), the temperature was raised to 500°C at a rate of 10°C / min and calcined at this temperature for 30 min. The thickness of the obtained electrode layer was about 15 μm, the electrode layer was uniform, dense and crack-free, and had good bonding with the CoSb3 thermoelectric material.
[0048] Example 5
[0049] An aluminum electrode layer was obtained on the CoSb3 bulk material according to the method of Example 1, except that in step (1), 20 g of three raw material powders (aluminum powder (35%), aluminum oxide powder (60%), and ammonium chloride powder (5%)) were weighed according to the mass percentage. The thickness of the obtained electrode layer was about 55 μm, and the electrode layer was uniform, dense, and crack-free, and had good bonding with the CoSb3 thermoelectric material.
[0050] Comparative Example 1
[0051] An electrode layer is obtained on the CoSb3 bulk material according to the method of Example 1, except that in step (3), the temperature is increased to 450°C at a heating rate of 10°C / min and calcined at this temperature for 2h.
[0052] Figure 6 This is a scanning electron microscope photograph of the interface of the obtained electrode / CoSb3 thermoelectric material. It can be seen from the figure that due to the low heat treatment temperature, no continuous electrode layer is formed on the surface of CoSb3, and the electrode function cannot be played.
[0053] Comparative Example 2
[0054] An electrode layer is obtained on the CoSb3 bulk material according to the method of Example 1, except that in step (3), the temperature is increased to 600°C at a heating rate of 10°C / min and calcined at this temperature for 2h.
[0055] Figure 7 This is a scanning electron microscope photograph of the interface of the obtained electrode / CoSb3 thermoelectric material. It can be seen from the figure that due to the high heat treatment temperature, the electrode layer formed on the CoSb3 surface is of poor quality and loose structure, and cracks appear inside the CoSb3 matrix.
[0056] Comparative Example 3
[0057] An electrode layer was obtained on the CoSb3 bulk material according to the method of Example 1, except that in step (1), 20 g of three raw material powders (aluminum powder (15%), aluminum oxide powder (77%), and ammonium chloride powder (8%)) were weighed according to the mass percentage. It was found that due to the low content of aluminum powder and the high content of ammonium chloride, the aluminum powder was excessively consumed by ammonium chloride, resulting in the formation of almost no electrode layer on the surface of CoSb3.
Claims
1. A method for connecting a skutterudite thermoelectric material to an electrode, characterized in that: The skutterudite thermoelectric material electrode is made of the following raw materials in percentage by weight: 25-35% aluminum powder, 3-5% ammonium chloride powder, and the remainder alumina powder; and comprises the following steps: (1) putting uniformly mixed aluminum powder, aluminum oxide powder and ammonium chloride powder into a crucible, and then burying the skutterudite thermoelectric material into the mixed powder; (2) Place the crucible into a quartz tube and evacuate and seal it; (3) raising the quartz tube to a calcination temperature for calcination, cooling it after calcination, taking out the skutterudite thermoelectric material, and obtaining an electrode layer on its surface; The particle size of aluminum powder is less than or equal to 10 microns, and the particle size of aluminum oxide powder is less than or equal to 1 micron; The calcination temperature is 500-550°C and the calcination time is 0.5-2h.
2. The connection method according to claim 1, characterized in that: The crucible is a graphite crucible.
3. The connection method according to claim 1, characterized in that: Aluminum powder, alumina powder and ammonium chloride powder are mixed evenly by wet mixing, and the solvent used is ethanol.
4. The connection method according to claim 1, characterized in that: The skutterudite thermoelectric material is buried in the center of the mixture powder.
5. The connection method according to claim 1, characterized in that: The skutterudite thermoelectric material is CoSb3 or a doped CoSb3 material.